SYNCHRONISM OF LATE PLEISTOCENE GLACIAL CYCLES WITH INSOLATION VARIATIONS ON THE EQUATOR - Vakulenko N.V.; Monin A.S.; Sonechkin D.M.; Kotlyakov V.M. (My University, 2007)
We show that Late Pleistocene glacial cycles were synchronous with frequency-modulated insolation variations on the equator related to changes in the Earth’s orbit eccentricity. The glacial stages of these cycles coincided with periods of a synchronous decrease in insolation of Polar regions in both hemispheres. Interglacials coincided with periods of a simultaneous increase in insolation due to changes in the Earth’s obliquity.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен